South African panorama: the novels of Daphne Rooke - Coetzee, Paulette June (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1998)
This thesis covers Daphne Rooke's eight published "South African" novels: A Grove of Fever Trees, Mittee, Ratoons, Wizards' Country, A Lover for Estelle, The Greyling, Diamond Jo, and Margaretha de la Porte. It supports the recent revival of critical interest in Rooke, and argues for the continuing relevance of her work in post-apartheid South Africa. This study also broadens the scope of recent Rooke research by including lesser known works like The Greyling and Margaretha de la Porte in its analysis. Recent criticism has focused on Rooke's unusual blend of romance and realism. The first three chapters concentrate more on "realism", emphasising the depth and extent of Rooke's engagement with serious social issues. The novels are examined in terms of their handling of the themes of class (chapter one), race (chapter two) and gender (chapter three). The concluding chapter shifts in focus to "romance" and examines the question of generic_identity -- touching on Rooke's gothic, magical realist and "popular" qualities -within a consideration of the particular "South African-ness" of her work.
Keywords: Rooke, Daphne, 1914- -- Criticism and interpretation